The functional graphene/epoxy resin composites prepared by novel two-phase extraction towards enhancing mechanical properties and thermal stability - Zhu, Wenfeng; Wang, Qianxi; Zhang, Pengchao; Li, Lei; Zhang, Li; Li, Houbu; Ding, Lekang; Jin, Zunlong; Li, Peipei; Zhang, Jiaoxia (Frontiers in Chemistry, 2024)
Epoxy resins are one of the most widely used thermosetting resins due to their excellent properties. However, epoxy resins are prone to brittle fracture, which restricts their application and development. In this work, graphene oxide is firstly prepared by the Hummer method, then modified by hyperbranched polyamide ester, and reduced by hydrazine hydrate to obtain functionalized graphene, which improves the compatibility between graphene and epoxy resin. The different ratios of functionalized graphene/epoxy composites were prepared by a novel two-phase extraction method, and their mechanical properties and thermal stability were tested. The results showed that the mechanical properties of functionalized graphene/epoxy composites were greatly improved, in which the tensile strength of the functionalized graphene/epoxy composites with a mass fraction of 0.1wt% was increased by 77wt% over that of the pure epoxy resin, the flexural strength was increased by 56%, and the glass transition temperature was also increased by 50°C.